An Anatomy of the World: dissezioni metafisiche e corrispondenze reinventate in un’elegia funebre di John Donne - Gallo, Carmen (Status Quaestionis, 2013)
An Anatomy of the World (1611) is one of most famous poetical work by the Metaphysical poet John Donne, often quoted for its lines about the disorder caused by the so-called new science. The poem presents itself as belonging to the genre of the obsequies, and displays a complex meditation on man and universe and their dying condition as a consequence of the Fall. The pivotal metaphor of the poem is the anatomy of this dead world, whose dissection and investigation recalls the argumentative style of the anatomy as Elizabethan genre. Through the analysis of some literary and scientific registers and images, the paper investigates how Donne tries to invent a sort of negative correspondence between macrocosm and microcosm, sustained by the discoveries of the new science, in which the Neo-Platonic order is substituted by the ubiquitous disorder of Sin.